High-power few-cycle Cr:ZnSe mid-infrared source for attosecond soft x-ray physics - Leshchenko, Vyacheslav E.; Talbert, Bradford K.; Lai, Yu Hang; Li, Sha; Tang, Yaguo; Hageman, Stephen J.; Smith, Greg; Agostini, Pierre; DiMauro, Louis F.; Blaga, Cosmin I. (My University, 2020)
The development of mid-infrared, high-energy pulses of extremely short pulse duration is of great importance to the strong-field physics community, as it enables extension of the high-harmonic cutoff towards the keV range of photon energies. Here we demonstrate a Cr2+:ZnSe laser amplifier delivering 7 mJ, 100 fs pulses at 1 kHz repetition rate and 2.4 µm central wavelength with excellent energy stability and beam quality. These pulses are post-compressed to 39 fs, 6.2 mJ, and 115 GW peak power in a novel nonlinear compression scheme. The laser system was used to generate coherent soft x-ray radiation up to 0.6 keV covering the entire water window, which is of high importance for bio-relevant applications. The obtained results open a wide range of applications in nonlinear optics, attosecond and strong-field physics, and remote sensing.